Associations between interoceptive sensitivity, intuitive eating, and body mass index in patients with anorexia nervosa and normal‐weight controls. (9th April 2019) - Richard, Anna; Meule, Adrian; Georgii, Claudio; Voderholzer, Ulrich; Cuntz, Ulrich; Wilhelm, Frank H.; Blechert, Jens
Abstract: Reduced perception of bodily signals and low levels of intuitive eating have been reported in patients with anorexia nervosa (AN) compared with normal‐weight individuals. However, findings have been inconsistent and treatment progress might account for some of these inconsistencies. Thirty‐seven inpatients with AN and 39 normal‐weight controls completed a heartbeat perception task and the Intuitive Eating Scale–2. Patients with AN reported lower intuitive eating than controls, whereas interoceptive sensitivity did not differ between groups. Higher interoceptive sensitivity was related to higher intuitive eating across both groups. In patients with AN, both higher interoceptive sensitivity and intuitive eating correlated with the number of days in the hospital and with higher body mass index (BMI), when controlling for BMI at admission. These relationships suggest that interoceptive sensitivity and intuitive eating improve during treatment. Future research should determine whether these improvements promote weight gain or follow it.